Descriptive analysis of 1,048 presentations in the first five years of a zero-suicide framework in a child and youth mental health service in Australia - Branjerdporn, Grace; McCosker, Laura K.; Jackson, Derek; Gillespie, Kerri M.; McDowell, Sarah; Chand, Sandeep; Joshi, Hitesh; Pisani, Anthony R.; Stapelberg, Nicolas J. C.; Welch, Matthew; Turner, Kathryn; Woerwag-Mehta, Sabine (Frontiers in Psychiatry, 2024)
Suicide in children is a significant and unacceptable global phenomenon. This paper provides a descriptive overview of the children presenting in the first five years (2016-2021) of the implementation of the Zero Suicide Framework (ZSF) and Suicide Prevention Pathway (SPP) at a Child and Youth Mental Health Service in Queensland, Australia. Basic demographic variables (sex, age, socioeconomic status), and changes in presentations over time, are presented for 1,048 children. . Completeness of selected SPP components relating to care planning and universal interventions are examined as an indicator of fidelity to the SPP model of care. The paper then focuses on the cohort of children who received care through the SPP in 2020, describing their demographic characteristics and baseline clinical scores. There was an increase in admissions each year and children presented with a diverse range of clinical needs. The aim is to inform the use of the ZSF/SPP in child mental health settings globally.